Implementation of backend and web application solution to assist athletic performance measuring through the use of IMU sensors - Papageorgiou, A. (Aristotle University of Thessaloniki, 2020)
This paper analyzes the application of Internet of Things (IoT) technologies in athletic performance evaluation (coaching), focusing on the web and server application aspect of technologies. The sport of choice for this analysis is Ten Pin Bowling. To demonstrate IoT application in coaching Bowling, first a desired functionality requirements list was compiled based on bowling coaches` feedback and a study of the sport`s mechanics in general. Given the feedback and after studying the available IoT technologies on the market, the most fitting ones were selected for use in development. A big focus for this selection was technology scalability and innovation while sticking to the open-source community as much as possible. After the research, we built and extensively documented a web and a server application to serve as part of the frontend and cloud infrastructure respectively of a larger IoT solution called Athlos Bowling. This resulted in a TRL5 software solution that after being put to the test is ready to be used as an assisting tool in coaching bowling. The outcome of this product proves the impact IoT can have on the sport of Bowling and sport science in general.